Policy measures for creating an integrated and brand-focused innovation system for film industries in shadow nations: an application to Australia's national film industry. (1st January 2013) - Maher, Sean; Brambini, Annalisa; Vang, Jan
Shadow nations face particular problems in constructing competitive film industries. Shadow nations refer to nations whose relative competitiveness suffers from easy product substitutability by products initiated, produced and distributed by powerful actors, such as media conglomerates located in Hollywood. The dominant literature has so far neglected the developing policy recommendations for dealing explicitly with the challenges of shadow nations. This paper aims to develop and apply a normative model for the development of film industries in shadow nations. The model integrates insights from innovation system studies and place branding. The developed model is applied to the Australian film industry as Australia represents a typical shadow nation within the film industry.